Inference on Cooperative Learning Strategy and Academic Achievement of Physics Students in Girei LGA, Adamawa State - Idi, Danjuma; Stephen, Mathew; Michael, Ibrahim (Lembaga Yasin AlSys, 2024)
This study examined the effectiveness of cooperative learning strategy on secondary school students' academic achievement in physics. Guided by two research questions and three hypotheses, the study employed a quasi-experimental design and was conducted with a sample of 60 Senior Secondary School year two (SS2) physics students from Government Senior Secondary School Girei, Adamawa State. The Physics Achievement Test (PAT) was used to collect data, which were then analyzed using descriptive and inferential statistics. The results showed a significant mean score difference of 13.78333 (p < 0.001) favoring the cooperative learning group over the conventional group. Gender differences were significant in the conventional group (t-statistic = -20.696, p < 0.001), with males scoring higher, but not in the cooperative group (t-statistic = -35.658, p = 0.425). Thus, cooperative learning appears to reduce the gender gap in physics achievement. It is recommended that workshops be held to train teachers on effective cooperative learning strategies.